KONSEPTUALISASI EKONOMI PADA DEBAT CALON WAKIL PRESIDEN 2024: KAJIAN LINGUISTIK KOGNITIF - Nurul Hanna Fauziyyah; Sofia Sofia (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to identify and analyze the types of conceptual metaphors used by the vice-presidential candidates in the 2024 debate to interpret the concept of the economy in constructing linguistic reality. The research employs a descriptive qualitative approach with data consisting of metaphorical expressions found in the 2024 vice-presidential debate. The data were collected using the observation method, specifically the non-participatory observation and note-taking techniques, and were analyzed using the referential identity (matching) method. The results reveal four main conceptual metaphors underlying the economic discourse, namely: (1) THE ECONOMY IS A PLANT/ORGANISM, (2) THE ECONOMY IS A MECHANICAL MACHINE, (3) THE ECONOMY IS A LIQUID IN A CONTAINER, and (4) THE ECONOMY IS A PRISONER. These findings demonstrate that conceptual metaphors not only represent the cognitive ways of thinking of the speakers but also function as rhetorical tools used to shape public perception. Keywords: conceptual metaphor, economy, vice-presidential debate, cognitive linguistics Abstrak: Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis jenis-jenis metafora konseptual yang dgunakan para calon wakil presiden dalam debat untuk memaknai konsep ekonomi dalam mewujudkan realitas bahasa. Penelitian ini menggunakan pendekatan kualitatif deskriptis dengan data berupa ungkapan metaforis yang terdapat dalam debat calon wakil presiden tahun 2024. Data dikumpulkan menggunakan metode simak dan teknik simak libat cakap dan teknik catat, kemudian dianalisis menggunakan metode padan. Hasilnya, terdapat empat metafora konseptual yang mendasari wacana ekonomi tersebut, yaitu: 1) EKONOMI ADALAH TUMBUHAN/ORGANISME. 2) EKONOMI ADALAH MESIN MEKANIK, 3) EKONOMI ADALAH CAIRAN DALAM WADAH, dan 4) EKONOMI ADALAH NARAPIDANA. Temuan ini membuktikan bahwa metafora konseptual bukan hanya merepresentasikan cara berpikir secara kognitif seorang penutur, tetapi juga menjadi alata retoris yang digunakan untuk emembentuk persepsi publik. Kata Kunci: metafora konseptual, ekonomi, debat cawapres, linguistik kognitif